2009
DOI: 10.1084/jem.20081761
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus (EBV)–encoded small RNA is released from EBV-infected cells and activates signaling from toll-like receptor 3

Abstract: Epstein-Barr virus–encoded small RNA (EBER) is nonpolyadenylated, noncoding RNA that forms stem-loop structure by intermolecular base-pairing, giving rise to double-stranded RNA (dsRNA)–like molecules, and exists abundantly in EBV-infected cells. Here, we report that EBER induces signaling from the Toll-like receptor 3 (TLR3), which is a sensor of viral double-stranded RNA (dsRNA) and induces type I IFN and proinflammatory cytokines. A substantial amount of EBER, which was sufficient to induce signaling from T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
249
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(256 citation statements)
references
References 28 publications
4
249
1
2
Order By: Relevance
“…TLR2, 3 and 9 sense EBV particles (Gaudreault et al, 2007;Iwakiri et al, 2009;van Gent et al, 2011), yet no evidence for TLR4-mediated recognition of EBV has been reported (Gaudreault et al, 2007). Here, we monitored the influence of BGLF5 on TLR2 and TLR4.…”
Section: Silencing Bglf5 Expression In Ebv-producing B Cellsmentioning
confidence: 99%
“…TLR2, 3 and 9 sense EBV particles (Gaudreault et al, 2007;Iwakiri et al, 2009;van Gent et al, 2011), yet no evidence for TLR4-mediated recognition of EBV has been reported (Gaudreault et al, 2007). Here, we monitored the influence of BGLF5 on TLR2 and TLR4.…”
Section: Silencing Bglf5 Expression In Ebv-producing B Cellsmentioning
confidence: 99%
“…Several TLRs, including TLR2, TLR3, and TLR9, participate in recognition of EBV by monocytes/macrophages and dendritic cells. 5,7,11,12 Gaudreault et al 7 revealed that stimulation of monocytes with EBV virions leads to the release of MCP-1 and IL-8 through the activation of TLR2. 7 TLR2 recognizes glycoproteins of the viral envelope, resulting in the activation of NF-kB signaling and production of these inflammatory cytokines.…”
Section: Lf Expression Levels Correlated Inversely With Mcp-1 and Il-mentioning
confidence: 99%
“…10 Several reports have demonstrated that human TLRs can recognize EBV. 5,7,11,12 Stimulation of human monocytes with either inactivated or infectious EBV virions leads to the release of MCP-1 and to an increase of several cytokine mRNA levels, including IL-8, through the engagement of the cell surface TLR2. 7 More recently, TLR9 was found to contribute to the recognition of EBV DNA in primary monocytes, leading to an increased release of IL-8.…”
mentioning
confidence: 99%
“…It was demonstrated that EBERs induce expression of type-I IFNs by binding to the retinoic acid-inducible gene I (RIG-I) product that is a cytosolic protein that recognizes viral dsRNA inside the cell (Samanta et al, 2006). Another evidence of a role of EBERs in innate immunity is their binding to Toll-like receptor 3 after secreted from EBV-infected cells (Iwakiri et al, 2009;Iwakiri and Takada, 2010), triggering innate immunity that might explain immunopathologic diseases caused by active EBV infection. However, EBERs also induce an anti-infl ammatory cytokine, IL-10, through RIG-1-mediated interferon regulatory factor (IRF) 3 (Samanta et al, 2008), suggesting that modulation of innate immune signaling by EBERs may contribute to EBVmediated oncogenesis.…”
Section: Treatment Strategies For the Patients With Ebv-associated Chlmentioning
confidence: 99%
“…Nt (Ho et al, 1999;Komano et al, 1999;Kitagawa et al, 2000;Yamamoto et al., 2000;Iwakiri et al, 2003;Iwakiri et al, 2005;Samanta et al, 2006;Samanta et al, 2008;Iwakiri et al, 2009;Iwakiri and Takada, 2010 Immunization with LMP1 gene or polyepitope expression vectors Taylor et al, 2004;Smith et al, 2006;Pan et al, 2009;Lutzky et al, 2010;Chia et al, Immunization with LMP2A gene or polyepitope expression vectors (Taylor et al, 2004;Smith et al, 2006;Pan et al, 2009;Lutzky et al, 2010;Chia et al, 2011) LMP2B Modulation of innate immune response nt TLR: Toll-like receptor, RIG: retinoic acid-inducible gene, PKR: RNA-dependent protein kinase, Nt: not tested, CTL: cytotoxic T lymphocyte, DC: dendritic cells.…”
Section: Inhibition Of Apoptosis (Pkr)mentioning
confidence: 99%